Grappling with the challenges of measuring women's economic empowerment in intrahousehold settings. (August 2020) - Laszlo, Sonia; Grantham, Kate; Oskay, Ecem; Zhang, Tingting
Highlights: We consider different measures of women's economic empowerment (WEE) in the context of intrahousehold models. Many measures of agency (decision making, psychosocial measures, norms) can directly map into the intrahousehold bargaining power parameter. Achievement measures (e.g. labour market or educational outcomes) are indirect as they are also determined by factors unrelated to empowerment. A multi-disciplinary literature highlights the complexity of measuring WEE in three key domains (labour market, control over resources, family) Abstract: Defining and measuring women's economic empowerment (WEE) has been at the centre of the current debates among international development scholars and practitioners. The lack of clear consensus on both may limit widespread efforts to design and evaluate programs and policies aimed at improving women's well-being. Building on intra-household allocation models and on Sen (1989) and Kabeer (1999), this paper proposes a conceptual framework of intrahousehold decision-making which can accommodate many classes of WEE measures. It proposes a typology of WEE measures which combines proximity of concept to measurability. Findings from a review of the scholarly literature between 2005 and 2020 are then presented to demonstrate the diversity of published approaches that exist to measure WEE.